The genus Cascoplecia Poinar, 2010 (Diptera: Bibionidae: Cascopleciinae) from mid-Cretaceous Myanmar amber, with description of two new species - Skartveit, John (Zootaxa, 2026)
The genus Cascoplecia Poinar, 2010 from mid-Cretaceous Myanmar amber is revised, and two new species described. Cascoplecia tridens sp. nov. is described from a female specimen, whereas C. gracilis sp. nov. is described from a male specimen, the first male Cascoplecia known.